2017
DOI: 10.1016/j.ultrasmedbio.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Image Classification of Ductal Carcinoma In Situ (DCIS) of the Breast: Analysis of 705 DCIS Lesions 1

Abstract: The Japan Association of Breast and Thyroid Sonology (JABTS) proposed, in 2003, a conceptual classification system for non-mass abnormalities to be applied in addition to the conventional concept of masses, to facilitate detecting ductal carcinoma in situ (DCIS) lesions. The aim of this study was to confirm the utility of this system and to clarify the distribution of these findings in DCIS lesions. Data on 705 surgically treated DCIS lesions from 16 institutions in Japan were retrospectively reviewed. All 705… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 24 publications
1
39
0
2
Order By: Relevance
“…In Japan Association of Breast and Thyroid Sonology (JABTS) BC-02 study, US image classification for DCIS was reported. The most frequent findings were hypo-echoic areas in the mammary gland (48.6%), followed by solid masses (28.0%) and duct abnormalities (10.2%) or mixed masses (8.1%) ( 25 ). Specific findings of US to predict mixed invasive cancer are halo-positive masses and interruption of the interface between the adipose tissue and gland ( 26 ).…”
Section: Standard Treatment For Dcismentioning
confidence: 99%
“…In Japan Association of Breast and Thyroid Sonology (JABTS) BC-02 study, US image classification for DCIS was reported. The most frequent findings were hypo-echoic areas in the mammary gland (48.6%), followed by solid masses (28.0%) and duct abnormalities (10.2%) or mixed masses (8.1%) ( 25 ). Specific findings of US to predict mixed invasive cancer are halo-positive masses and interruption of the interface between the adipose tissue and gland ( 26 ).…”
Section: Standard Treatment For Dcismentioning
confidence: 99%
“…There were 705 DCIS cases collected throughout the BC-02 study, of which 260 cases (36.9%) were masses and 428 cases (60.7%) were non-mass abnormalities. In the remaining 17 cases (2.4%), masses and non-mass abnormalities were coexistent to the same degree and could not be classified as one or the other [2]. Details of the findings were as follows: hypoechoic areas in the mammary gland were found to be the most frequent lesion (48.6%) of DCIS lesions, followed by solid masses (28%) and abnormalities of the ducts (10.2%) or mixed masses (8.1%).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 12, when DCIS lesions are present in relatively thick ducts, they can be observed as abnormalities of the ducts, and when these advance into thin ducts and lobules, they may be observed as hypoechoic areas [2].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our experience, ultrasonographic findings in DCIS were mottled/heterogeneous parenchyma with increased vascularity on Doppler, multiple intra cystic solid masses, and peripheral dilated ducts with irregular wall and echogenic contents. Watanabe T et al [15] found that the most frequent ultrasonographic findings in DCIS were hypoechoic areas, followed by solid masses, abnormalities of the ducts or mixed masses, distortion, multiple small cysts, and echogenic foci without a hypoechoic area also were reported. The ultrasound features of DCIS have been described in the literature; however, the classifications vary slightly among authors.…”
Section: Discussionmentioning
confidence: 99%